Choroidal neovascularisation triggered multiple evanescent white dot syndrome (MEWDS) in predisposed eyes. Issue 7 (28th September 2017) - Mathis, Thibaud; Delaunay, Benoit; Cahuzac, Armelle; Vasseur, Vivien; Mauget-Faÿsse, Martine; Kodjikian, Laurent
Abstract : Background: Multiple evanescent white dot syndrome (MEWDS) is an inflammatory disease that can be associated with choroidalneovascularisation (CNV). However, few studies in the literature have described the occurrence of MEWDS in association with CNV. This paper discusses whether CNV can trigger MEWDS in a predisposed eye. Methods: A retrospective multicentric case series of six eyes in six patients with acute onset of MEWDS and evidence of previous CNV was conducted between January 2015 and January 2017. All patients underwent ophthalmic examination including multimodal imaging at baseline and during follow-up. Results: The mean age was 32.2±12.2 years. The majority of patients were women (5/1). In each case, MEWDS was diagnosed during a recurrence or occurrence of CNV secondary to choriocapillaritis, central serous chorioretinopathy or atrophic scar, presumably due to congenital toxoplasmosis. All patients were treated with intravitreal injections of antivascular endothelial growth factor (anti-VEGF) with good anatomical and functional responses (mean gain of 0.3±0.31logMAR). The mean duration of follow-up was 13.5±10.65 months. Conclusion: This study highlights a sequence in the development of MEWDS, following the occurrence or recurrence of CNV. CNV may trigger MEWDS, possibly due to the proinflammatory environment created by the retinal tissue surrounding the CNV.